Global Phenomenon: The Millennial Generation is Trapped by Sandwich Generation in Indonesia - Wahyu Trisno Aji; Faizah harani (International Journal of Educational and Psychological Sciences, 2023)
This study is a theoretical exploration of the global phenomenon related to the millennial generation trapped in the sandwich generation. The term sandwich generation, was first introduced by Dorothy Miller in her paper entitled "The Sandwich Generation Adult Children Of the Aging" in 1981. In theory, the sandwich generation is a group of adults aged 30-40 years who take care not only of their children but also of their children parents. Be it physically, emotionally or financially. Caring for elderly parents or children also has a negative impact on a person's physical and mental health, moreover the care and treatment is carried out intensively. The approach used in this study is a descriptive approach adopted from descriptive and analytical qualitative research methods, by using library data and documentation. This feature contains a detailed description, critical and comparative thinking, as well as a systematic evaluation of the available data relating to the subject matter. In addition, the research methods used can also be described as interdisciplinary. It can thus help create a unique perspective for tackling a chosen topic by thinking and analyzing across the traditional boundaries that define an established academic discipline.